1999
DOI: 10.1161/01.str.30.10.2008
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Good Recovery in Patients With the Most Severe Strokes?

Abstract: Background and Purpose-Even patients with the most severe strokes sometimes experience a remarkably good recovery.We evaluated possible predictors of a good outcome to search for new therapeutic strategies. Methods-We included the 223 patients (19%) with the most severe strokes (Scandinavian Stroke Scale score Ͻ15 points) from the 1197 unselected patients in the Copenhagen Stroke Study. Of these, 139 (62%) died in the hospital and were excluded. The 26 survivors (31%) with a good functional outcome (Barthel In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
1
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 30 publications
5
95
1
9
Order By: Relevance
“…This report is in consonance with those of Cullen et al [9] and Jorgensen et al [25] These studies suggested that less aggressive care for the elderly by family members and health care providers was responsible for poor functional outcome, while the presence of a spouse was a strong predictor of a good functional outcome in young patients with the most severe strokes. [25] High-risk lifestyle behaviors [2] such as cigarette smoking, alcohol and/or substance abuse, and physical inactivity when associated with diabetes mellitus, hyperlipidemia, homocysteinemia, hypertension, atherogenic dyslipidemia, visceral obesity, impaired fibrinolysis, and left ventricular dysfunction, individually and collectively, contribute to poor outcome in renal, metabolic, cerebrovascular, and/or cardiovascular events. It is, therefore, hoped that with the identification of many prognostic factors by this study supported by those of earlier studies, health care providers would be able to improve the outcome of coma.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This report is in consonance with those of Cullen et al [9] and Jorgensen et al [25] These studies suggested that less aggressive care for the elderly by family members and health care providers was responsible for poor functional outcome, while the presence of a spouse was a strong predictor of a good functional outcome in young patients with the most severe strokes. [25] High-risk lifestyle behaviors [2] such as cigarette smoking, alcohol and/or substance abuse, and physical inactivity when associated with diabetes mellitus, hyperlipidemia, homocysteinemia, hypertension, atherogenic dyslipidemia, visceral obesity, impaired fibrinolysis, and left ventricular dysfunction, individually and collectively, contribute to poor outcome in renal, metabolic, cerebrovascular, and/or cardiovascular events. It is, therefore, hoped that with the identification of many prognostic factors by this study supported by those of earlier studies, health care providers would be able to improve the outcome of coma.…”
Section: Discussionsupporting
confidence: 91%
“…32.5% (65) of the patients who presented after 6 h were referred from primary and secondary health facilities with a mortality rate of 89.6%, while the other 12.5% (25) brought in directly from their homes had a mortality rate of 68.7% (χ 2 =1.00, P=0.00).…”
Section: Resultsmentioning
confidence: 99%
“…(See Table 3) However this influence was only at discharge from hospital. This finding is similar to that of Jorgensen et al (1999) and Pohjahsvaara et al (1997) who established that younger patients have better functional outcomes at discharge from hospital and that older patients deteriorate significantly more in activities of daily living. Functional independence more than six weeks post discharge was not dependent on the patient's age (p = 0.37).…”
Section: Results and Discussion Study Populationsupporting
confidence: 88%
“…Furthermore, early improvement was significantly associated with a good outcome. Spontaneous recovery and association with good outcome is well documented in stroke [17][18][19] although in comparison to this group of patients, previous studies included either only moderate 19 or very severe stroke. 19 The relationship between early improvement and outcome, across the range of stroke severity studied here, in patients within each clinical syndrome has not previously been documented.…”
Section: Discussionmentioning
confidence: 99%
“…6,17 We therefore dichotomised patients into 'improvers' and 'non-improvers', dependent on their rate of recovery at day 4, and the recovery patterns of these sub-groups were distinct from one another. Furthermore, early improvement was significantly associated with a good outcome.…”
Section: Discussionmentioning
confidence: 99%